Clinical Trials: The Role of Regulatory Agencies, Pharmacovigilance Laws, Guidelines, Risk Management, Patenting, and Publicizing Results - Venkataramana Kandi; Sabitha Vadakedath; Purna Singh Addanki; Vikram Godishala; Venkata Bharatkumar Pinnelli (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The research carried out to find a better treatment, improve healthcare, and benefit the current medical practice is termed clinical research. Clinical trial includes the pharmacodynamics (mechanisms of action of a new drug), pharmacokinetics (drug metabolism inside the body), therapeutics (efficacy of the drug), and adverse effects (safety of the drug) of the novel medical products. Clinical research is a process that involves human subjects and their biological specimens. The clinical trial is a meticulously planned protocol-based study of a drug/device to discover a new/better way to prevent, diagnose, and treat a disease/illness. Considering the involvement of both healthy and diseased people in clinical trials, the regulatory authorities have a significant role in the processes involving the conduction of clinical research and carefully evaluate their potential implications on humans. Because clinical trials are usually aimed at assessing the safety and efficacy of novel pharmaceutical compounds and medical devices, pharmacovigilance laws and risk management assume increased significance while conducting clinical research/trials. In this review, we attempt to discuss the regulatory authorities' roles in different geographical regions, including the United States of America, The European Union, and India. We also focus on the importance of pharmacovigilance laws and risk management during clinical trials.